The Implementation of Goal Programming Method in the Optimization of Furniture Production at UD JK Aluminium in Blitar Regency - Prisma Brilliana; Susi Setiawani; Lioni Anka Monalisa; Arif Fatahillah; Saddam Hussen (Pancaran Pendidikan, 2022)
Goal Programming is a method of solving problems by allocating company resources with several objectives to obtain an optimal solution. The solution can be obtained by using the QM for Windows program. The results showed that the objective function could be achieved well. The solution to the problem obtained from the QM For Windows application was that the optimal value for the budget cost of the window, storefront, and wardrobe raw materials was the same as the budget cost that had been issued by the furniture production owner, which was Rp. 22,850.000,00 per month. Then the upper limit can be minimized to raw material from aluminum (b1), which was 28.1 meters from the original 610 meters. In order to reach the target of the production process, the average working hours was 55 hours. For a good and correct production volume recommendation, the number of products produced must be optimal to produce 20 units of products consisting of 10 units of windows, five units of show windows, and five wardrobe units per month.